Modeling and Simulation of NFC Logical Layer Peer-to-Peer Mode using CPN and TA - Saeed Ghasemi; Leili Mohammad Khanli; Mina Zolfi; Ghader Tahmasebpour (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Network communication technologies have been growing explosively due to the increasing demand on faster and simpler communication; hence, providing new communication technologies is a challenging task. To make this task easy, many researchers have developed different network modeling and simulation tools with different characteristics. In this paper, simulation of Near Field Communication (NFC) logical layer control protocol is proposed to investigate efficiency of NFC device in peer-to-peer mode. For this purpose, Colored Petri Net (CPN) and Timed Automata (TA) have been used for analyses. According to the results, CPN was better than TA for simulating NFC logical layer control protocol because it could provide more details on complex communication network.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5154